Asymmetrical ultrafiltration membranes based on polylactic acid for the removal of organic substances from wastewater. (February 2022) - Khalil, Hiyam; Hegab, Hanaa M.; Nassar, Lobna; Wadi, Vijay S.; Naddeo, Vincenzo; Yousef, Ahmed F.; Banat, Fawzi; Hasan, Shadi W.
Abstract: The continued use of non-biodegradable polymeric-based membranes for water purification has led to an unsustainable accumulation of waste at disposal, resulting in various environmental problems. In this study, eco-friendly asymmetric ultrafiltration (UF) membranes were fabricated from polylactic acid (PLA) with different polymer concentrations using the phase inversion method. The fabricated membranes were characterized using Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), scanning electron microscopy (SEM), contact angle, porosity, and pore size analysis. Permeate flux and organic matter (bovine serum albumin (BSA)) rejection were evaluated using synthetic wastewater. The anti-fouling properties of PLA membranes were investigated through static adsorption and dynamic filtration of BSA. Furthermore, the performance of the best performing PLA membrane was evaluated via chemical oxygen demand (COD) rejection as well as membrane fouling using raw municipal wastewater obtained from a local wastewater treatment plant (WWTP) in Abu Dhabi (UAE). The results indicated that increasing the PLA concentration to 20 wt% improved BSA removal from synthetic and raw wastewaters by up to 92 and 89%, respectively, in addition to improving the membrane anti-fouling property. The post-filtration and after cleaning FT-IR spectra revealed high antifouling property with no detection of BSA peaks, SEM images confirmed the reduction in membrane's pore size as PLA concentration increased, resulting in enhancing the antifouling properties of the membranes. In conclusion, this study demonstrated that PLA-UF membranes could be a viable eco-friendly alternative to traditional crude oil-derived membranes. Graphical abstract: Unlabelled Image Highlights: Eco-friendly asymmetric UF PLA membranes were fabricated and tested. PLA membranes improved BSA and COD removal by up to 92 and 89%, respectively. PLA membranes demonstrated very good anti-fouling properties with 89% FRR. The increase in PLA concentration enhanced anti-fouling properties.